Ferronickel water electrolysis oxygen production catalyst as well as preparation method and application thereof

A nickel-iron catalyst with a carbon nanotube structure addresses the limitations of noble metal catalysts by improving electron transfer and reducing overpotential, offering a cost-effective solution for oxygen evolution reaction.

CN119243240APending Publication Date: 2025-01-03SHENZHEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411422212.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing noble metal catalysts for oxygen evolution reaction (OER) such as iridium oxide and ruthenium oxide face issues of high overpotential, poor durability, high cost, and scarcity, limiting their widespread use.

Method used

A nickel-iron water electrolysis oxygen production catalyst is developed using folic acid and non-noble metal iron-nickel agents, with controlled synthesis to achieve a carbon nanotube structure where Ni single atoms are doped and Fe2O3 nanoparticles are distributed, enhancing electron transfer and catalytic efficiency.

Benefits of technology

The catalyst exhibits excellent OER performance with reduced overpotential (230mV in 1M KOH) and low cost, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243240A_ABST
    Figure CN119243240A_ABST
Patent Text Reader

Abstract

The invention relates to a ferronickel water electrolysis oxygen production catalyst and a preparation method and application thereof. According to the nickel-iron water electrolysis oxygen production catalyst, the carbon nano tube serves as a carbon matrix, Ni single atoms are evenly doped in the carbon nano tube, Fe2O3 nano particles are evenly distributed on the surface of the carbon nano tube, and the performance of a FeNi bimetallic catalyst is further improved. The ferro-nickel water electrolysis oxygen production catalyst is applied to alkaline OER reaction, the overpotential of 10 mA / cm < 2 > in 1 M KOH is only 230 mV, the performance is far better than that of commercial RuO2, and the ferro-nickel water electrolysis oxygen production catalyst has wide industrial application value and prospect. Meanwhile, folic acid and a non-noble metal iron-nickel agent are used as raw materials for preparing the ferro-nickel water electrolysis oxygen production catalyst, the price is low, a hydrothermal preparation method is adopted, simpleness and high efficiency are achieved, the electrode preparation cost is greatly reduced, and industrial application is quite facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a nickel-iron water electrolysis oxygen production catalyst and a preparation method and application thereof. Background Art

[0002] The oxygen evolution reaction (OER) is a key half-reaction in a variety of energy conversion devices, such as water electrolysis and electrochemical carbon dioxide reduction. Iridium oxide (IrO2) and ruthenium oxide (RuO2) have long been considered as top electrocatalysts for the oxygen evolution reaction (OER), but their suboptimal durability, high price, and scarcity limit the widespread use of these catalysts.

[0003] In this regard, a large number of non-precious metal-based electrocatalysts have also been studied in the prior art, especially the first group transition elements represented by Fe / Ni oxides or hydroxides. The electrical conductivity of iron species such as Fe2O3 and FeOOH is poor, and improving their electrical conductivity can greatly improve their OER activity. The strong electronic interaction between Ni and Fe is the key to the excellent OER activity of NiFe-based catalysts compared to single Fe and single Ni. Carbon materials have good electrical conductivity and high chemical stability as carriers. However, carbon materials with relatively inert surfaces can only provide weak electronic interactions with supported metal nanoparticles. Doping non-metallic dopants on carbon substrates and functionalization of oxygen-containing groups on carbon surfaces are two widely used methods for changing the carbon surface to allow metal nanoparticles to bind tightly. Therefore, the development of catalysts with low overpotential, excellent catalytic efficiency and low cost is a key issue that needs to be solved urgently. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of difficulty in long-term high-efficiency electrolysis of water to produce oxygen, too high overpotential, high cost, etc. in the prior art of noble metal catalysts for oxygen evolution reaction (OER) such as iridium oxide and ruthenium oxide, thereby providing a nickel-iron water electrolysis oxygen production catalyst, which has excellent catalytic efficiency in the oxygen evolution reaction, is prepared with folic acid and non-noble metal iron-nickel agent as raw materials, has mild reaction conditions and low cost.

[0005] In order to solve the above technical problems, the present invention is implemented through the following technical solutions.

[0006] The first aspect of the present invention provides a method for preparing a nickel-iron water electrolysis oxygen production catalyst, comprising the following steps:

[0007] (1) dissolving the iron source and the nickel source in the folic acid solution, stirring and ultrasonically dispersing them uniformly;

[0008] (2) adding hydrazine monohydrate and dispersing by ultrasonication to obtain a mixed solution;

[0009] (3) heating the mixed solution obtained in step (2) for reaction;

[0010] (4) After the heating reaction is completed, centrifuge the reaction, wash the precipitate, and freeze-dry it to obtain a sample.

[0011] Preferably, the folic acid solution in step (1) is prepared by the following steps: adding folic acid to a solvent and stirring the mixture evenly.

[0012] Preferably, the solvent is selected from one or more of ethanol and water; more preferably, the solvent is selected from an ethanol-water mixed solvent; most preferably, the solvent is selected from an ethanol-water mixed solvent, wherein the volume ratio of ethanol to water is 1:0.1-1.

[0013] Preferably, the water is selected from one or more of deionized water, distilled water and purified water.

[0014] Preferably, the molar volume ratio of folic acid to solvent is 0.005-0.02:1.

[0015] It should be understood that, unless otherwise specified, the "amount-to-volume ratio" in the context of the present invention should be understood in a conventional manner in the art, that is, the ratio of the amount of solid substance (in mmol) to the volume of liquid (in mL). For example, when the "amount-to-volume ratio of folic acid to solvent is 0.01:1", if the amount of folic acid added is 0.2 mmol, the amount of solvent added is 20 mL.

[0016] Preferably, the iron source in step (1) is selected from one or more of ferric nitrate, ferric sulfate, ferric acetate, ferric citrate, ferric chloride and ferric bromide; more preferably, the iron source is selected from ferric nitrate; most preferably, the iron source is selected from iron (III) nitrate nonahydrate.

[0017] Preferably, the nickel source in step (1) is selected from one or more of nickel chloride, nickel bromide, nickel nitrate, nickel acetate, and nickel sulfate; more preferably, the nickel source is selected from nickel chloride; most preferably, the nickel source is selected from nickel (II) chloride hexahydrate.

[0018] Preferably, the molar ratio of the iron element in the iron source to the nickel element in the nickel source in step (1) is 1:1.1-2; more preferably, the molar ratio of the iron element in the iron source to the nickel element in the nickel source in step (1) is 1:1.2-1.8; most preferably, the molar ratio of the iron element in the iron source to the nickel element in the nickel source in step (1) is 1:1.5.

[0019] Preferably, the molar ratio of folic acid in the folic acid solution in step (1) to the iron element in the iron source is 1-8.4:1; more preferably, the molar ratio of folic acid in the folic acid solution in step (1) to the iron element in the iron source is 3-6:1; most preferably, the molar ratio of folic acid in the folic acid solution in step (1) to the iron element in the iron source is 5:1.

[0020] Preferably, the molar ratio of folic acid in the folic acid solution in step (1) to the nickel element in the nickel source is 2-8:1; more preferably, the molar ratio of folic acid in the folic acid solution in step (1) to the nickel element in the nickel source is 2.5-5:1; most preferably, the molar ratio of folic acid in the folic acid solution in step (1) to the nickel element in the nickel source is 3.33:1.

[0021] Preferably, the molar volume ratio of folic acid in the folic acid solution in step (1) to hydrazine monohydrate in step (2) is 0.025-0.125:1.

[0022] Preferably, the heating reaction in step (3) is carried out at a temperature of 140-200° C. and for a time of 2-4 h.

[0023] Preferably, the washing in step (4) is specifically: washing 1-5 times with an ethanol-water mixed solvent.

[0024] Preferably, the freeze-drying time in step (4) is 48-72 hours and the temperature is -50 to -100°C.

[0025] The second aspect of the present invention provides a nickel-iron water electrolysis oxygen production catalyst prepared according to the above preparation method.

[0026] Preferably, the nickel-iron water electrolysis oxygen production catalyst is a carbon nanotube structure, wherein Ni single atoms are uniformly doped in the carbon nanotubes, and Fe2O3 nanoparticles are uniformly distributed on the surface of the carbon nanotubes.

[0027] Preferably, the Fe2O3 nanoparticles have a particle size of 10-15 nm.

[0028] The third aspect of the present invention provides the use of the nickel-iron water electrolysis oxygen production catalyst prepared according to the above preparation method in the water electrolysis oxygen production reaction.

[0029] Compared with the prior art, the present invention has the following technical effects:

[0030] Doping single metal atoms incorporated into the carbon matrix has been shown to be more effective for activating inert carbon surfaces for electron transfer. More importantly, these single metal atoms can have strong electronic interactions with the loaded nanoparticles. During the synthesis of the carbon matrix (folic acid), FA and metal-FA undergo synergistic banded hydrogen bond self-assembly in a mixed solvent, and the metal and folic acid are coordinated to self-assemble. The present invention strictly controls the dosage ratio of folic acid to metal so that it can self-assemble to form carbon nanotubes, thereby avoiding the reduction of catalytic performance caused by the formation of carbon nanosheets and other forms. At the same time, by strictly controlling the dosage ratio of Fe and Ni, the particle size of Fe2O3 nanoparticles can be controlled between 10-15nm, Ni single atoms are uniformly doped in carbon nanotubes, and Fe2O3 nanoparticles are uniformly distributed on their surface. The electron transfer between Ni and Fe is enhanced, further improving the performance of the FeNi bimetallic catalyst. The nickel-iron electrolysis water oxygen production catalyst of the present invention is applied to alkaline OER reaction, and at 10mA / cm in 1M KOH 2 The overpotential is only 230mV, which is much better than commercial RuO2 and has broad industrial application value and prospects. At the same time, the raw materials used in the preparation of the nickel-iron electrolysis water oxygen production catalyst of the present invention are folic acid and non-precious metal iron-nickel agent, which are low in price and adopt a hydrothermal preparation method, which is simple and efficient, greatly reducing the cost of electrode preparation and is very conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 1 and 2 are LSV curves of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention and RuO2 catalyst in 1M KOH electrolyte.

[0032] Figure 2 Schematic diagram of the morphology of the catalysts of the embodiments of the present invention and the comparative examples, wherein Figure 2 a is a schematic diagram of the results of Example 1, Figure 2 b is a schematic diagram of the results of comparative example 1, Figure 2 c is a schematic diagram of the results of comparative example 2, Figure 2 d is a schematic diagram of the results of comparative example 3.

[0033] Figure 3 XRD diagrams of the catalyst prepared in Example 1 of the present invention and the catalyst prepared in Comparative Example 1.

[0034] Figure 4 This is the spherical aberration electron microscope image of the present invention. Figure 4 a is the spherical aberration diagram of the catalyst prepared in Example 1, Figure 4 b The spherical aberration diagram of the catalyst prepared in Comparative Example 1.

[0035] Figure 5 The transmission electron microscope images and particle size analysis images of Example 1 and Comparative Example 1 of the present invention are shown in FIG. Figure 5 a-5b is the analysis result of Example 1, Figure 5 c-5d is the analysis result of comparative example 1, Figure 5 e-5f is the analysis result of comparative example 4.

[0036] Figure 6 It is a theoretical calculation diagram of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0038] Example 1

[0039] A nickel-iron water electrolysis oxygen production catalyst, the preparation method of which comprises the following steps:

[0040] (1) 0.25 mmol of folic acid was added to 13.5 mL of ethanol-deionized water mixed solvent (the volume ratio of ethanol to deionized water was 8:5.5) and ultrasonically stirred to obtain a folic acid solution; 0.05 mmol of iron (III) nitrate nonahydrate and 0.075 mmol of nickel (II) chloride hexahydrate were dissolved in the folic acid solution and ultrasonically dispersed to obtain a folic acid solution.

[0041] (2) Add 2 mL of hydrazine monohydrate and disperse by ultrasonic to obtain a mixed solution.

[0042] (3) The mixed solution obtained in step (2) was placed in a reaction kettle and heated to 140° C. in an oven for 2 h.

[0043] (4) After the heating reaction is completed, centrifugation is performed, and the precipitate is washed three times with an ethanol-deionized water mixed solution, and then freeze-dried for 48 hours to obtain a nickel-iron electrolysis water oxygen production catalyst named Fe:Ni:FA-0.4:0.6:2. Its morphology is shown in the figure Figure 2 -a as shown.

[0044] Example 2

[0045] A nickel-iron water electrolysis oxygen production catalyst, the preparation method of which comprises the following steps:

[0046] (1) 0.25 mmol of folic acid was added to 13.5 mL of ethanol-deionized water mixed solvent (the volume ratio of ethanol to deionized water was 8:5.5) and ultrasonically stirred to obtain a folic acid solution; 0.08 mmol of iron (III) nitrate nonahydrate and 0.1 mmol of nickel (II) chloride hexahydrate were dissolved in the folic acid solution and ultrasonically dispersed to obtain a folic acid solution.

[0047] (2) Add 2 mL of hydrazine monohydrate and disperse by ultrasonic to obtain a mixed solution.

[0048] (3) The mixed solution obtained in step (2) was placed in a reaction kettle and heated to 140° C. in an oven for 2 h.

[0049] (4) After the heating reaction is completed, centrifugation is performed, and the precipitate is washed three times with an ethanol-deionized water mixed solution, and then freeze-dried for 48 hours to obtain a nickel-iron water electrolysis oxygen production catalyst.

[0050] Example 3

[0051] A nickel-iron water electrolysis oxygen production catalyst, the preparation method of which comprises the following steps:

[0052] (1) 0.3 mmol of folic acid was added to 13.5 mL of ethanol-deionized water mixed solvent (the volume ratio of ethanol to deionized water was 8:5.5) and ultrasonically stirred to obtain a folic acid solution; 0.05 mmol of iron (III) nitrate nonahydrate and 0.08 mmol of nickel (II) chloride hexahydrate were dissolved in the folic acid solution and ultrasonically dispersed to obtain a folic acid solution.

[0053] (2) Add 2 mL of hydrazine monohydrate and disperse by ultrasonic to obtain a mixed solution.

[0054] (3) The mixed solution obtained in step (2) was placed in a reaction kettle and heated to 140° C. in an oven for 2 h.

[0055] (4) After the heating reaction is completed, centrifugation is performed, and the precipitate is washed three times with an ethanol-deionized water mixed solution, and then freeze-dried for 48 hours to obtain a nickel-iron water electrolysis oxygen production catalyst.

[0056] Comparative Example 1

[0057] A nickel-iron water electrolysis oxygen production catalyst, the preparation method of which comprises the following steps:

[0058] (1) 0.25 mmol of folic acid was added to 13.5 mL of ethanol-deionized water mixed solvent (the volume ratio of ethanol to deionized water was 8:5.5) and ultrasonically stirred to obtain a folic acid solution; 0.0375 mmol of iron (III) nitrate nonahydrate and 0.0875 mmol of nickel (II) chloride hexahydrate were dissolved in the folic acid solution and ultrasonically dispersed to obtain a folic acid solution.

[0059] (2) Add 2 mL of hydrazine monohydrate and disperse by ultrasonic to obtain a mixed solution.

[0060] (3) The mixed solution obtained in step (2) was placed in a reaction kettle and heated to 140° C. in an oven for 2 h.

[0061] (4) After the heating reaction is completed, centrifugation is performed, and the precipitate is washed three times with an ethanol-deionized water mixed solution, and then freeze-dried for 48 hours to obtain a nickel-iron electrolysis water oxygen production catalyst named Fe:Ni:FA-0.3:0.7:2. Its morphology is shown in the figure Figure 2 -b as shown.

[0062] Comparative Example 2

[0063] A nickel-based water electrolysis oxygen production catalyst, the preparation method of which comprises the following steps:

[0064] (1) 0.125 mmol of folic acid was added to 13.5 mL of ethanol-deionized water mixed solvent (the volume ratio of ethanol to deionized water was 8:5.5) and ultrasonically stirred to obtain a folic acid solution; 0.05 mmol of iron (III) nitrate nonahydrate and 0.075 mmol of nickel (II) chloride hexahydrate were dissolved in the folic acid solution and ultrasonically dispersed to obtain a folic acid solution.

[0065] (2) Add 2 mL of hydrazine monohydrate and disperse by ultrasonic to obtain a mixed solution.

[0066] (3) The mixed solution obtained in step (2) was placed in a reaction kettle and heated to 140° C. in an oven for 2 h.

[0067] (4) After the heating reaction is completed, centrifugation is performed, and the precipitate is washed three times with an ethanol-deionized water mixed solution, and then freeze-dried for 48 hours to obtain a nickel-based water electrolysis oxygen production catalyst named Fe:Ni:FA-0.4:0.6:1. Its morphology is shown in the figure Figure 2 -c.

[0068] Comparative Example 3

[0069] An iron-based water electrolysis oxygen production catalyst, the preparation method of which comprises the following steps:

[0070] (1) 0.5 mmol of folic acid was added to 13.5 mL of ethanol-deionized water mixed solvent (the volume ratio of ethanol to deionized water was 8:5.5) and ultrasonically stirred to obtain a folic acid solution; 0.05 mmol of iron (III) nitrate nonahydrate and 0.075 mmol of nickel (II) chloride hexahydrate were dissolved in the folic acid solution and ultrasonically dispersed to obtain a folic acid solution.

[0071] (2) Add 2 mL of hydrazine monohydrate and disperse by ultrasonic to obtain a mixed solution.

[0072] (3) The mixed solution obtained in step (2) was placed in a reaction kettle and heated to 140° C. in an oven for 2 h.

[0073] (4) After the heating reaction is completed, centrifugation is performed, and the precipitate is washed three times with an ethanol-deionized water mixed solution, and then freeze-dried for 48 hours to obtain an iron-based water electrolysis oxygen production catalyst named Fe:Ni:FA-0.4:0.6:4. Its morphology is shown in the figure Figure 2 -d as shown.

[0074] Comparative Example 4

[0075] An iron-based water electrolysis oxygen production catalyst, the preparation method of which comprises the following steps:

[0076] (1) 0.25 mmol of folic acid was added to 13.5 mL of ethanol-deionized water mixed solvent (the volume ratio of ethanol to deionized water was 8:5.5) and ultrasonically stirred to obtain a folic acid solution; 0.0625 mmol of iron (III) nitrate nonahydrate and 0.0625 mmol of nickel (II) chloride hexahydrate were dissolved in the folic acid solution and ultrasonically dispersed to obtain a folic acid solution.

[0077] (2) Add 2 mL of hydrazine monohydrate and disperse by ultrasonic to obtain a mixed solution.

[0078] (3) The mixed solution obtained in step (2) was placed in a reaction kettle and heated to 140° C. in an oven for 2 h.

[0079] (4) After the heating reaction is completed, centrifugation is performed, and the precipitate is washed three times with an ethanol-deionized water mixed solution, and then freeze-dried for 48 hours to obtain an iron-based water electrolysis oxygen production catalyst named Fe:Ni:FA-0.5:0.5:2.

[0080] Verification Example 1

[0081] The catalysts prepared in Example 1 of the present invention and Comparative Examples 1-4 were respectively taken, and the commercially available RuO2 catalyst was taken as a control, and the oxygen production catalytic performance of the five catalysts was tested respectively. The specific steps are as follows:

[0082] Take 2 mg of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 and the commercially available RuO2 catalyst, dissolve 2 mg of the catalyst in 200 μl of deionized water and 200 μl of ethanol, mix, then ultrasonicate for 10-20 min to prepare ink, and evenly drop the ink onto a 1*1 cm 2 On carbon paper, after drying, it is used as an electrode.

[0083] A three-electrode test system was used, with mercury / mercuric oxide as the reference electrode, platinum sheet as the counter electrode, the catalysts prepared in Example 1 and Comparative Examples 1-4, and commercially available RuO2 catalyst as the working electrodes, respectively, and the electrolyte was 1M KOH solution. The linear scan of the current versus voltage was performed using an electrochemical workstation at a scan rate of 10 mV / s. The larger the current at the same voltage, the better the oxygen production effect of water electrolysis. The test results are shown in Figure 2. Figure 1 shown.

[0084] The results show that the catalytic activity of the nickel-iron water electrolysis oxygen production catalyst prepared in Example 1 is much better than the catalysts prepared in Comparative Examples 1, 2, 3 and 4, as well as the commercially available RuO2 catalyst. The overpotential of the catalyst Fe:Ni:FA-0.4:0.6:2 prepared in Example 1 is 230mV, the overpotential of the Fe:Ni:FA-0.3:0.7:2 catalyst prepared in Comparative Example 1 is 260mV, the overpotential of the Fe:Ni:FA-0.4:0.6:1 catalyst prepared in Comparative Example 2 is 255mV, the overpotential of the Fe:Ni:FA-0.4:0.6:4 catalyst prepared in Comparative Example 3 is 259mV, the overpotential of the FeNiFA-0.5:0.5:2 catalyst prepared in Comparative Example 4 is 258mV, and the overpotential of the RuO2 catalyst is 270mV.

[0085] from Figure 2 It can be seen that the catalysts Fe:Ni:FA-0.4:0.6:1 prepared by adjusting the folic acid ratio in Comparative Example 2 and Fe:Ni:FA-0.4:0.6:4 prepared in Comparative Example 3 are in the form of nanosheets rather than carbon nanotubes. Figure 1 It can be seen that the performance of the samples in the form of nanosheets deteriorates.

[0086] X-ray diffractometer was used to characterize the two groups of catalysts with carbon nanotube morphology. Figure 3-4 The results show that the two catalysts, Fe:Ni:FA-0.4:0.6:2 in Example 1 and Fe:Ni:FA-0.3:0.7:2 in Comparative Example 1, do not show diffraction peaks of metallic nickel, but only diffraction peaks of metallic iron, and the metallic peak of Fe indicates that the Fe in the catalyst exists in the form of Fe2O3 particles, and Ni has no metallic diffraction peak. Figure 4 The spherical aberration electron microscope image further shows that Fe is in the form of Fe2O3 particles and Ni exists in the form of single atoms (so the X-ray diffractometer does not show the diffraction peak of metallic nickel).

[0087] from Figure 5 Come and see, Figure 5-ab indicates the particle size of Fe:Ni:FA-0.4:0.6:2 catalyst, the particle size of Fe2O3 is 13.21nm, Figure 5 -cd shows the particle size of Fe:Ni:FA-0.3:0.7:2 catalyst, the particle size of Fe2O3 is 9.43nm, Figure 5 -ef indicates the particle size of Fe:Ni:FA-0.5:0.5:2 catalyst, and the particle size of Fe2O3 is 17.34nm. According to the performance test results, Fe2O3 particle size that is too large or too small will lead to a significant decrease in the catalytic performance of the catalyst (see Figure 1 The reason is that the change in the FeNi ratio changes the particle size, and the change in particle size affects the coordination number of the surface metal atoms, thereby changing the binding energy with the oxygen evolution reaction intermediates. By controlling the Fe2O3 particle size to 10-15nm, the Fe2O3 particles with a suitable coordination number optimize the binding energy with the oxygen evolution reaction intermediates, reduce the reaction energy barrier, and thus improve its OER performance (see Figure 6 ).like Figure 1 The performance of Fe:Ni:FA-0.4:0.6:2 shown is better than that of Fe:Ni:FA-0.3:0.7:2.

[0088] From the above, it can be seen that the nickel-iron water electrolysis oxygen production catalyst prepared by the present invention can replace the traditional precious metal catalyst for electrocatalytic oxygen production reaction. At the same time, due to its simple preparation process and low cost, it has extremely high social and economic benefits and can be suitable for large-scale industrial production.

[0089] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.

Claims

1. A method for preparing a nickel-iron water electrolysis oxygen production catalyst, characterized in that: The steps include: (1) dissolving the iron source and the nickel source in the folic acid solution, stirring and ultrasonically dispersing them uniformly; (2) adding hydrazine monohydrate and dispersing by ultrasonication to obtain a mixed solution; (3) heating the mixed solution obtained in step (2) for reaction; (4) After the heating reaction is completed, centrifuge, take the precipitate, wash it and freeze-dry it to obtain the product.

2. The preparation method according to claim 1, characterized in that: The iron source in step (1) is selected from one or more of ferric nitrate, ferric sulfate, ferric acetate, ferric citrate, ferric chloride and ferric bromide.

3. The preparation method according to claim 1, characterized in that: The nickel source in step (1) is selected from one or more of nickel chloride, nickel bromide, nickel nitrate, nickel acetate and nickel sulfate.

4. The preparation method according to claim 1, characterized in that: The molar ratio of folic acid in the folic acid solution in step (1) to iron in the iron source is 1-8.4:

1.

5. The preparation method according to claim 1, characterized in that: The molar ratio of folic acid in the folic acid solution in step (1) to nickel element in the nickel source is 2-8:

1.

6. The preparation method according to claim 1, characterized in that: The molar volume ratio of folic acid in the folic acid solution of step (1) to hydrazine monohydrate in step (2) is 0.025-0.125:

1.

7. The preparation method according to claim 1, characterized in that: The heating reaction temperature in step (3) is 140-200° C. and the time is 2-4 hours.

8. The preparation method according to claim 1, characterized in that: The freeze-drying time in step (4) is 48-72 hours, and the temperature is -50 to -100°C.

9. A nickel-iron water electrolysis oxygen production catalyst prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the nickel-iron water electrolysis oxygen production catalyst prepared by the preparation method according to any one of claims 1 to 8 in the water electrolysis oxygen production reaction.